Study Of Biochemical And Molecular Polymorphisms Of Glucose-6-Phosphate Dehydrogenase Enzyme (Journal of Pharmaceutical Negative Results, 2023)
Genetic screening was carried out for Masalli area of Azerbaijan Republic for 23 school students and found different degree of enzyme deficiency for G6PD enzyme (activity between 0-60%). Enzyme preparations were made according with WHO requirements of erythrocytes from identified students with enzymatic activity deficiency, and were identified biochemically specific for three classes out of existing five: 13 students – the 2nd class, 6 students – the 3rd class, and 4 students – the 4th class.Complying to the 2nd class requirements, 24 family members of the school student F.N. (index patient) from Bedalan town were screened for G6PD enzyme deficiency, and 6 of them showed acute enzyme activity deficit (lower than 10%).DNA molecular analysis, isolated from blood of the F.N. index patient, was classified as the 2nd class of G6PD enzyme deficiency, and showed the substitution of Guanine nucleotide with Adenine in position 1178. As a result of the mutation in protein in the position 393, substitution of amino acids Arginine with Histidine [G6PD, 1178 (G-A) Arg393His] takes place.